Strategies for Convection Industry toward Competitive Advantage: A SWOT Approach - Susilawati, Susilawati; Pahrudin, Pahrudin; Zain, Rohaeniyah; Sholihah, Isfi; Agustina, Gina (Universitas Hamzanwadi, 2024)
This study aims to analyse business development strategies in increasing revenue in the convection industry of UP. Busana Butik. In an effort to compete in a dynamic market and face various challenges such as fluctuations in raw material prices, intense competition, and rapid changes in fashion trends, companies need to implement effective and efficient strategies. The research method used was qualitative with a descriptive approach carried out through observation, interviews and documentation to explain the research object directly. The steps in this study were carried out systematically through the SWOT analysis method to identify the strengths, weaknesses, opportunities, and threats faced by the company. Data was collected through interviews with the person in charge, head of production division and employees, as well as direct observation in the field. Based on internal and external analysis confirmed through SWOT analysis, UP Butik Fashion is in quadrant I, which indicates an aggressive position where the company can use its opportunities and strengths to attract more customers and increase revenue to maintain this aggressive position. UP. Butik Fashion can improve the quality of its products to produce durable and high-quality goods, expand promotional strategies to reach a wider audience, follow rapidly increasing demand, improve operational efficiency and reduce production costs through cooperation with the supply chain, continue to conduct market research and follow the latest trends, and provide job opportunities for experts in the field of convection. Thus, these strategies are expected to help UP. Butik Fashion achieve more significant growth in the convection industry